Metformin: A Novel Weapon Against Inflammation - Bai, Bo; Chen, Haibo (Frontiers in Pharmacology, 2021)
It has become widely accepted that inflammation is a driving force behind a variety of chronic diseases, such as cardiovascular disease, diabetes, kidney disease, cancer, neurodegenerative disorders, etc. However, the existing nonsteroidal anti-inflammatory drugs show a limited utility in clinical patients. Therefore, the novel agents with different inflammation-inhibitory mechanisms are worth pursuing. Metformin, a synthetic derivative of guanidine, has a history of more than 50 years of clinical experience in treating patients with type 2 diabetes. Intense research efforts have been dedicated to proving metformin’s inflammation-inhibitory effects in cells, animal models, patient records, and randomized clinical trials. The emerging evidence also indicates its therapeutic potential in clinical domains other than type 2 diabetes. Herein, this article appraises current pre-clinical and clinical findings, emphasizing metformin’s anti-inflammatory properties under individual pathophysiological scenarios. In summary, the anti-inflammatory effects of metformin are clearly evident in pre-clinical models. By comparison, there are still clinical perplexities to be addressed in repurposing metformin to inflammation-driven chronic diseases. Future randomized controlled trials, incorporating better stratification/targeting, would establish metformin’s utility in this clinical setting.